DAMPAK OPERASIONAL PEMBANGKIT LISTRIK TENAGA DIESEL (PLTD) TELAGA TERHADAP KUALITAS AIR - Mahmud, Marike (Sainstek, 2007)
This research aims to get drawing about environment condition of PLTD activity, especially water quality condition that for further will be analyzed. The result of the soil water quality can be the basis of estimating the impact in which may be resulted and for further may be useful to determine the processing attempt. The result of this research shows waste water quality in which found in PLTD pipe, whether before or after processing of physical parameter, especially TSS more than standard quality of liquid waste of the industry activity KEP-Men 51/MENLH/10/1995. And so does the chemical parameter, DO,BOD,COD, phenol and oil do not fulfill the standard quality by which is conditioned. Moreover , the physical quality of water source in which is used by community as drinking water seen that TDS in over than the limitation by the health ministry of RI verdict Numb.907/MENKES/SK/VII/2002. Meanwhile, for chemical quality it is cane be said that for water is gotten from well there are oil and phenol. It decreases DO walue and increase BOD then it does not fulfill standard quality condition by which is settled.